Biology teaching that develops the metacognitive aspect of learning: How to learn competence - Labak, Irena; Maruncek, Ivona; Blazetic, Senka (Journal of Education and e-Learning Research, 2024)
Higher-order thinking and metacognition are closely related and are part of learning to develop competence. The goal of this research was to determine the practice of teaching biology that develops metacognition and evaluate whether teachers require specific professional training for this purpose or if broader cognitive-focused training can also enhance metacognitive development in students. The original Teaching Observation Form (TOF) has been adapted for research objectives. A survey was designed to capture the subjective perspectives of 292 students and their teachers regarding metacognition development. Additionally, the research involved six biology teachers who were professionally trained in a program focused on higher-order thinking. The survey results indicate a self-assessed good teaching practice for the development of metacognition. However, analysis of the first lesson's video recordings showed that some components had been eliminated from biology classes which hindered students' ability to develop metacognition. Although higher-order thinking and metacognition are interconnected phenomena, professional development training focuses solely on higher-order thinking whose impact we established through analysis of other lessons does not induce the necessary positive changes for the comprehensive development of metacognition in students. In a nutshell, explicit professional development programs aimed at fostering metacognitive awareness among teachers need to be designed. These programs should instruct teachers on how to model the development of metacognition in students through their teaching.